The McKinsey edge : success principles from the world's most powerful consulting firm / Shu Hattori. - Hattori, Shu (McGraw-Hill, 2016)
Whether youre climbing your way up the corporate ladder; starting on the very first rung; or feeling stuck somewhere in the middle; this practical guide presents rigorously selected; battle-tested tips that will give you the edge you need to up your game; raise your profile; and take your career to the next level using a proven four-step program. --